Effects of retinoic acid on testicular lipids with polyunsaturated fatty acid during ex vivo tissue maintenance - Sanchez Chaves, Manuela (2023)
In vitro spermatogenesis has been successfully achieved by utilizing a gas-liquid interphase culture system. Within this experimental framework, monitoring of lipid metabolism provides a deeper understanding of its significance within the spermatogenic process, thereby yielding valuable insights that could be applied to ex vivo spermatogenesis biotechnology. It is known that retinoic acid (RA) is required for spermatogonia differentiation, to complete the meiotic divisions in spermatocytes and to support the full development of spermatogenic cells into elongated spermatids. The molecular mechanism by which RA enhances the spermatogenesis process remains in part unknown. Here, we evaluated the effects of RA supplementation on testicular lipids with long-chain (C18-C22) polyunsaturated fatty acids (PUFA) during ex vivo spermatogenesis progression in prepuberal mouse testicular explants. An analysis of spermatogenic cell types in testis explants from 6-day-old mice cultured for 22 days revealed progress in the differentiation of spermatogonial stem cells to haploid round spermatids. After 44 days in culture, some sperm were detected. Notably, the incidence of spermatozoa per unit of tissue was higher in the presence of RA than in its absence. In addition, the explants exposed to RA had lower amounts of neutral lipids, especially triacylglycerols, than those cultured in basal medium. Moreover, the addition of RA led to a decrease in the proportion of uncommon PUFAs (20:3n-9 and 22:4n-9), which we had previously observed as accumulating in neutral lipids from explants cultured under basal conditions. Simultaneously, similar to what occurs in vivo, membrane glycerophospholipids and cholesterol esters increased their proportion of C20-C22 n-6 PUFA. These lipids changes were linked to an augmentation in testosterone production and an increase in the haploid cell in the explants supplemented with RA. The similarity between these lipid changes and those observed in vivo during normal testicular posnatal development underscores the pivotal role of RA in optimizing ex vivo spermatogenesis.